2022
DOI: 10.3390/hydrology9050085
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Treatment by a Dry Detention Basin with Stormwater Wetland Characteristics

Abstract: Dry detention basins (DB) are commonly used to reduce the rate of runoff in urban areas and may provide open space for recreation between storms. However, most are not effective at nitrogen removal in comparison to other measures, such as constructed wetlands. The study goal was to assess the nitrogen treatment efficiency of a DB that exhibited some wetland characteristics, including saturated soil near the inlet and wetland vegetation that covered 40% of the surface area. Influent and effluent samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The observed lower discharge during the warmer months was not a result of lower precipitation totals because the mean rainfall received during the warm months (June-August) was 15 cm, while during the cold months (January-March), it was 11 cm. A similar finding was observed in another study conducted in Eastern North Carolina, where it was concluded that evaporation and transpiration rates were greater during warm periods relative to colder periods and that resulted in less discharge during warmer months [12]. The mean pH of samples collected from the eight locations was slightly alkaline and during baseflow, ranged from 7.1 at site WO-2 to 7.4 at site WO-7, while during stormflow, the range was 7.1 (WO-3) to 7.7 (WO-1).…”
Section: Physicochemical Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…The observed lower discharge during the warmer months was not a result of lower precipitation totals because the mean rainfall received during the warm months (June-August) was 15 cm, while during the cold months (January-March), it was 11 cm. A similar finding was observed in another study conducted in Eastern North Carolina, where it was concluded that evaporation and transpiration rates were greater during warm periods relative to colder periods and that resulted in less discharge during warmer months [12]. The mean pH of samples collected from the eight locations was slightly alkaline and during baseflow, ranged from 7.1 at site WO-2 to 7.4 at site WO-7, while during stormflow, the range was 7.1 (WO-3) to 7.7 (WO-1).…”
Section: Physicochemical Characteristicssupporting
confidence: 87%
“…Stormwater control measures including bioretention, constructed wetlands, and/or detention basins are now required in many larger cities to slow the delivery of runoff and pollutants to streams [10][11][12]. However, many communities were developed prior to the required implementation of the control measures and thus the streams draining these watersheds may exhibit erosion, frequent flooding, and other characteristics symptomatic of "urban stream syndrome" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall was evenly distributed throughout the seasons (Supplemental), and differences in monthly precipitation were not significantly different (p = 0.464) when comparing warm (mean 11.8 cm/month) and cool (mean 10.0 cm/month) periods. Evapotranspiration rates are typically higher during the "growing season" spanning the spring and summer months (April-September) due to longer daylight hours, warmer temperatures, and active plant uptake and transpiration of water, thus resulting in lower discharge [36]. Differences in evapotranspiration may explain the higher inflow and outflows during cooler periods as the mean temperatures during fall and winter months (8.9 • C) were significantly (p < 0.001) lower relative to summer and spring (22.2 • C), thus resulting in less evaporation (Supplementary Materials).…”
Section: Flow Dynamicsmentioning
confidence: 99%
“…Like with the removal of phosphorus, the hydraulic retention time has been reported as a significant factor regarding bacteria removal [23]. Wetlands may be constructed in upland areas to mimic processes in natural wetland and to remove pollutants including nutrients and E. coli from wastewater [24,25,31,33], urban stormwater [24,[34][35][36], and agricultural drainage [30,37].…”
Section: Introductionmentioning
confidence: 99%
“…Pochwat and Pizzo [8] revealed that the use of a detention tank may significantly reduce the amount of sewage outfall from a drainage system, and that the method of connecting the device to a network has an influence on its efficiency. Humphrey et al [9] evaluated the nitrogen treatment efficiency of a detention basin (DB) that exhibited some wetland characteristics. The findings from their study suggest that the TN treatment efficiency of DBs may be improved by incorporating wetland characteristics.…”
mentioning
confidence: 99%